Optimizing voltage control in AC microgrid systems with fuzzy logic strategies and performance assessment - S. Adiche; M. Larbi; D. Toumi (Electrical engineering & Electromechanics)
Introduction. Microgrids (MGs) have garnered significant attention for their numerous advantages, providing a solution for powering remote and distant locations while enhancing system reliability. In MGs, distributed generation inverters generally operate in parallel with the droop control strategies. This study focuses on the approach based on the P-f/Q-V droop control technique with virtual impedance for AC MG management. Essentially, the virtual impedance loop aims to decouple reactive and active power control without the need for additional physical components. Novelty. This research proposes enhancing voltage control in AC MG systems by introducing new methods of various control strategies, including PI and Fuzzy Logic Controller (FLC), and evaluating the effectiveness of each approach. The mathematical model of a system is always an approximation of real systems, variations or errors between mathematical models and real systems are referred to as uncertainty. This concept of uncertainty is present in both signals and models. In our study, uncertainties may involve factors related to the filter LC components. By employing advanced control strategies like FLC, the purpose of this research aims to contribute to the optimization and reliability of AC MG systems through the improvement of voltage control, which leads to guaranteed equitable power-sharing. Results. The major advantages of the FLC are robustness for any variation on the system and fast response. MATLAB software is used to simulate and validate the suggested control. Practical value. The simulation results show that the suggested control performs better in precise tracking optimization and robustness for all disturbances on the system compared to a PI controller. References 24, table 5, figures 11.